Preventing blindness from diabetic retinopathy through community screening - Wani G Mena (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
Diabetic retinopathy (DR) is the commonest microvascular complication of diabetes and a leading cause of blindness in working age adults. The global prevalence of diabetic retinopathy is estimated at 34% and varies from region to region [1]. Its prevalence is increasing in Sub Saharan Africa and other low and middle low income countries, fuelled by the increasing number of people living in poverty with diabetes, poor control of blood sugar, lipids and blood pressure as well as lack of services for early detection and treatment of DR [2]. Blindness from DR is preventable through early detection and treatment of the sight threatening stages of retinopathy. However, many diabetic patients are not aware that they have retinopathy or that it can cause blindness. Patients therefore do not present to health care providers until symptoms appear, by which time treatment cannot restore lost sight. Symptoms only develop at a late stage in the disease and even patients with good diabetic control may develop retinopathy.